The Effect of Academic Self-Efficacy Training Toward The Nursing Students’ Academic Burnout Participating In Block-System Learning - Maria Lupita Nena Meo; I Gusti Ayu Pramitharesthi; Adriani Natalia M. (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: Dense block system and online learning during the covid-19 pandemic has led to complaints of boredom, tiredness and fatigue causing academic fatigue syndrome (academic burnout). Unresolved academic burnout will lead to a decline in academic achievement and decrease of interest in education. This also affects the performance of educational institutions. Therefore, it is necessary to take action to address academic burnout in students.  This research aims to determine the effect of academic self-efficacy training on academic burnout experienced by nursing students. Methods: The method used was quantitativequasy-experimental with Pre-test Post-test Design with control group. The research was conducted at two nursing education institutions in Indonseia during July-August 2020. A total of 90 research respondents were selected with simple random sampling technique.  The instrument used in this study was the Maslach Burnout Inventory-Student Survey (MBI-SS).  Research data was then analyzed using paired t test and Independet test. Results: Paired t test in the treatment group obtained p value = 0.000. This means that there is a difference in academic burnout before and after intervention in this group, while the test results in the control group obtained p value = 0.170 meaning that there is no difference before and after intervention. Independent t test result showed the value of p = 0.000, indicating differences in academic fatigue in these two groups. Conclusion: Academic efficacy training is effective in reducing academic burnout in nursing students who participated in lectures with the block system.